2011
DOI: 10.1016/j.watres.2011.01.015
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anoxia and anaerobia on ciliate community in biological nutrient removal systems using laboratory-scale sequencing batch reactors (SBRs)

Abstract: Please cite this article as: Dubber, D., Gray, N.F. The effect of anoxia and anaerobia on ciliate community in biological nutrient removal systems using laboratory-scale sequencing batch reactors (SBRs), Water Research (2011Research ( ), doi: 10.1016Research ( /j.watres.2011 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The positive correlation between the DO and the abundance of Aspidisca cicada contradicts the findings of Cingolani et al (1992), Cingolani and Ciccarelli (1997), Nicolau et al (2005Nicolau et al ( , 2007 and Dubber and Gray (2011a) who stated that Aspidisca cicada showed a remarkable ability to survive in adverse conditions. The crawling ciliates, as a group, also showed a significant positive association with the DO of the mixed liquor (0.62; n = 35), and Vorticella microstoma indicated the lack of DO with a significant coefficient value of −0.51 (n = 35) which can be explained by its good resistance to the influence of anoxic environment and environmental changes (Madoni 1994;Esteban et al 1991;Lee et al 2004;Dubber and Gray 2011b). Testate amoebae and Arcella sp.…”
Section: Discussionmentioning
confidence: 99%
“…The positive correlation between the DO and the abundance of Aspidisca cicada contradicts the findings of Cingolani et al (1992), Cingolani and Ciccarelli (1997), Nicolau et al (2005Nicolau et al ( , 2007 and Dubber and Gray (2011a) who stated that Aspidisca cicada showed a remarkable ability to survive in adverse conditions. The crawling ciliates, as a group, also showed a significant positive association with the DO of the mixed liquor (0.62; n = 35), and Vorticella microstoma indicated the lack of DO with a significant coefficient value of −0.51 (n = 35) which can be explained by its good resistance to the influence of anoxic environment and environmental changes (Madoni 1994;Esteban et al 1991;Lee et al 2004;Dubber and Gray 2011b). Testate amoebae and Arcella sp.…”
Section: Discussionmentioning
confidence: 99%
“…The paucity of polysaccharide export proteins could be explained if ciliates use exocytosis for polysaccharide export (Cheng and Hufnagel ; Gutierrez and Orias ; Turkewitz ). The studies reported here provide a wealth of novel information relevant to the ecology, evolution, physiology, and pathology of model ciliates and probably to the characteristics of many other ciliates of industrial and bioremediative importance (Dubber and Gray ; Gertler et al. ; Harikrishnan et al.…”
Section: Discussionmentioning
confidence: 99%
“…The peritrichs are responsible for water clarification by their bacterivory; hence, they are an ecologically important group in aquatic environments (9, 17, 29). The abundance of peritrichs is not often reported, and when planktonic, is difficult to interpret because they are either attached to algae in the plankton, or are in stages of telotroch, which are usually difficult to identify (see (28) and references therein).…”
mentioning
confidence: 99%